Association of serum IL12 with clinical and biochemical parameters in a cohort of diagnosed rheumatoid arthritis patients on oral conventional synthetic disease modifying anti-rheumatic drugs - Mushtaq, Iffat; Amir Rashid, Amir Rashid; Asifa Majeed, Asifa Majeed; Isma Riaz, Isma Riaz; Zunaira Ali Baig, Zunaira Ali Baig; Anoshia Javaid (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the association of serum interleukin-12 levels with disease progression in active rheumatoid arthritis patients on oral conventional synthetic disease-modifying anti-rheumatic drugs. Methods: The case-control study was conducted at the Army Medical College, Rawalpindi, in collaboration with the Pak Emirates Military Hospital, Rawalpindi, Pakistan, from January to December 2022, and comprised rheumatoid arthritis patients or either gender aged 18-75 years who were placed in group I, while group II comprised healthy controls. Demographic and clinical data was noted, and 2ml blood samples were drawn from each subject. The serum was separated and analysed using sandwich enzyme-linked immunosorbent assay to quantify serum interleukin-12 levels. Data was analysed using SPSS 22. Results: Of the 150 subjects, 75(50%) were in group I; 27(36%) makes and 48(64%) females with overall mean age 45.70±11.70 years. There were 75(50%) subjects in group II; 37(49.3%) males and 38(50.7%) females with overall mean age 31.70±7.70 years. Serum interleukin-12, erythrocyte sedimentation rate and C-reactive protein-quantitative levels were significantly higher in group I compared to group II (p<0.05). Smoking, positive family history of rheumatoid arthritis in a first-degree relative and history of consanguinity were identified as risk factors though they were not statistically significant (p>0.05). In group I (n=75), out of total study subjects, only 55(73.3%) cases belonged to the predominant castes, namely Awan, Rajput, Pathan, Araeen, Bhatti, Malik, Mughal, Sudhan, Chaudary, and Jutt. These individuals showed a significantly higher mean serum interleukin-12 levels compared to patients of other castes in the same group. Conclusion: Mean serum interleukin-12levelswere higher in rheumatoid arthritis patients despite being on oral conventional synthetic disease-modifying anti-rheumatic drugs. Key Words: Cytokines, Interleukin-12, Arthritis, Rheumatoid, Enzyme-linked immunosorbent assay.